Old Plants for New Food Products? The Diachronic Human Ecology of Wild Herbs in the Western Alps - Mousaab Alrhmoun; Aurora Romano; Naji Sulaiman; Andrea Pieroni (Plants)
This ethnobotanical study examines the traditional knowledge and usage patterns of wild plants in the western Alps, specifically within the Ubaye and Bellino Valleys, through a comparative analysis of data collected from 1983 (published in 1990) to 2024. Our study aims to assess the change in plant usage, species diversity, and the changing roles of plants in local traditions in the western Alpine mountain ecosystems. While the 1983 survey documented medicinal uses centered around pastoralist practices, the 2024 data highlight a notable increase in the use of synanthropic plants, now utilized both medicinally and as food. Several species such as Allium sativum, Artemisia absinthium, and Urtica dioica have shown resilience and continuity in local cultural practices, maintaining medicinal, culinary, and ritual significance across the four decades. The 1983 survey documented the greatest variety of species (101), a number that decreased in subsequent studies. The 2009 survey identified 36 species not previously recorded in 1983, and the 2024 field study noted an additional 20 species. The study highlights the economic potential of several wild species in these alpine areas, such as Achillea, Artemisia, Verbascum, Veronica, Viola, Polygonum, Bunium, and Sorbus spp., which could be utilized for creating new herbal teas, artisanal beers, liqueurs, ice creams, sweets, and seasoned food products. Expanding the uses of these plants could not only preserve ethnobotanical knowledge but also stimulate local economies and support sustainable development in alpine communities. The documented temporal shifts in plant usage reflect broader cultural, ecological, and socio-economic changes, underscoring the importance of preserving biodiversity and traditional knowledge amidst ongoing environmental and societal shifts. This study underlines the need to conserve ethnobotanical heritage while adapting to the evolving landscape of the region. Future research could focus on exploring the role of these species in broader sustainability initiatives, including conservation strategies, ecosystem services, and community-based tourism while continuing to document the cultural dynamics influencing plant usage.